Reconstruction of Arabic language education within the framework of the Kurikulum Merdeka: an ontological, epistemological, and axiological analysis - Mahjatin Nabilah Syarofina; Kamal Yusuf; Linura Tuada (Himpunan Pengembang Kurikulum Indonesia, 2026)
The transformation of Arabic language education within the Kurikulum Merdeka requires a comprehensive philosophical reconstruction to address ontological ambiguity, epistemological gaps, and unclear axiological orientations. This study aims to formulate the ontological foundations of Arabic language education in the Kurikulum Merdeka, develop an epistemological framework aligned with the Merdeka Belajar paradigm, and evaluate the axiological relevance of curriculum implementation to student competency development. This research employs a library-based method with descriptive analysis of policy documents, academic journals, and philosophical literature on Arabic language education. The findings propose a theoretical framework that reconceptualizes Arabic learning as a humanizing process emphasizing competency-based learning, Islamic-oriented constructivism, and character formation through the internalization of Pancasila values. The epistemological framework integrates project-based and problem-based learning with contextual digital resources to promote active knowledge construction. The axiological dimension highlights ethical communication, spiritual intellectualism, and learning oriented toward solving social issues. The reconstructed framework strengthens the teacher’s role as a facilitator of meaning and supports adaptive curriculum design responsive to learner needs. These findings are expected to serve as a theoretical foundation for the development of Arabic language curricula in Indonesia that are relevant, holistic, and sustainable. Abstrak Transformasi pendidikan bahasa Arab dalam Kurikulum Merdeka menuntut rekonstruksi filosofis yang komprehensif untuk mengatasi ketidakjelasan tujuan ontologis, dasar epistemologis, dan orientasi aksiologis pembelajaran. Kondisi ini menimbulkan kebutuhan mendesak untuk merekonstruksi kerangka teoretis yang komprehensif. Penelitian ini bertujuan menyusun konsep ontologi pendidikan bahasa Arab dalam Kurikulum Merdeka, merumuskan kerangka epistemologis pembelajaran sesuai paradigma Merdeka Belajar, serta menilai relevansi aksiologis penerapan kurikulum terhadap pengembangan kompetensi murid. Penelitian ini menggunakan metode studi pustaka dengan analisis deskriptif terhadap dokumen kebijakan, jurnal akademik, dan literatur filsafat pendidikan bahasa Arab. Hasil penelitian menunjukkan kerangka teoritis yang menempatkan pembelajaran bahasa Arab sebagai proses humanisasi yang menekankan pembelajaran berbasis kompetensi, konstruktivisme bernuansa islami, dan pembentukan karakter melalui internalisasi nilai profil pelajar Pancasila. Kerangka epistemologis yang dihasilkan mencakup integrasi metode proyek, pembelajaran berbasis masalah, dan pemanfaatan sumber belajar digital yang kontekstual. Dimensi aksiologis ditandai penguatan nilai etika komunikasi, spiritualitas keilmuan, dan orientasi pembelajaran pada pemecahan masalah sosial. Kerangka ini berimplikasi pada penguatan peran guru sebagai fasilitator makna dan desain kurikulum yang adaptif terhadap kebutuhan murid. Temuan penelitian diharapkan mampu menjadi landasan teori dalam pengembangan kurikulum bahasa Arab di Indonesia secara relevan dan berkelanjutan. Kata Kunci: filsafat pendidikan; Kurikulum Merdeka; pendidikan bahasa Arab; rekonstruksi